THEORY OF LEXICOLOGICAL SKILLS IN THE TEACHING AND LEARNING PROCESS - Yunusova, Sarvinoz Faxridinovna (INTERNATIONAL CONFERENCES, 2023)
This article is about the theory of lexicological skills which we use during the teaching period. In this period learning process is important as well. The ability to retrieve nine lexical components; instantly combine them with the preceding or following words. Keep in mind that there are no concrete descriptions of what constitutes a competence.